2000
DOI: 10.1074/jbc.275.20.15357
|View full text |Cite
|
Sign up to set email alerts
|

Normal Blood Pressure and Plasma Renin Activity in Mice Lacking the Renin-binding Protein, a Cellular Renin Inhibitor

Abstract: In renal extracts, some renin is present as "high molecular weight renin," a heterodimeric complex of renin with the 46-kDa renin-binding protein (RnBP), also known as N-acyl-D-glucosamine 2-epimerase. Because RnBP specifically inhibits renin activity, the protein was proposed to play an important role in the regulation of the renin-angiotensin system (RAS). Using gene targeting, we have generated mice lacking RnBP and tested this hypothesis in vivo. In particular, we analyzed biosynthesis, secretion, and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…50 Moreover, the same authors suggested a regulation of RnBP gene expression by oestradiol, and the intravenous injection of the RnBP into rats resulted in a rapid and strong inhibition of plasma renin activity that persisted for at least 2 h. However, knockout of the gene encoding for this protein in mice did not show any effect on RAS activity or blood pressure. 51 Therefore, more studies are necessary to understand the role of RnBP in the control of ovarian renin activity and AngII production.…”
Section: Discussionmentioning
confidence: 99%
“…50 Moreover, the same authors suggested a regulation of RnBP gene expression by oestradiol, and the intravenous injection of the RnBP into rats resulted in a rapid and strong inhibition of plasma renin activity that persisted for at least 2 h. However, knockout of the gene encoding for this protein in mice did not show any effect on RAS activity or blood pressure. 51 Therefore, more studies are necessary to understand the role of RnBP in the control of ovarian renin activity and AngII production.…”
Section: Discussionmentioning
confidence: 99%
“…72 Mice lacking RnBP display normal blood pressure and plasma renin activity. 73 Therefore, it is unlikely that this intracellular RnBP is a determinant of renin activity and/or metabolism in vivo.…”
Section: (Pro)renin Receptorsmentioning
confidence: 99%
“…9,23,24 One renin-binding protein identified in tissue homogenates is identical to N-acyl-D-glucosamine-2-epimerase, a cytosolic protein that inhibits renin in vitro but is not considered to participate in the RAS in vivo. 25 The M6P/insulin-like growth factor II receptor binds renin and prorenin with a K d of Ϸ1 nmol/L. 9 This receptor binds only glycosylated proteins with M6P residues.…”
Section: Renin-binding Proteinsmentioning
confidence: 99%